2015
DOI: 10.1126/scitranslmed.aaa3634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective LRRK2 kinase inhibition on nonhuman primate lung

Abstract: Inhibition of the kinase activity of leucine-rich repeat kinase 2 (LRRK2) is under investigation as a possible treatment for Parkinson's disease. However, there is no clinical validation as yet, and the safety implications of targeting LRRK2 kinase activity are not well understood. We evaluated the potential safety risks by comparing human and mouse LRRK2 mRNA tissue expression, by analyzing a Lrrk2 knockout mouse model, and by testing selective brain-penetrating LRRK2 kinase inhibitors in multiple species. LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
293
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(330 citation statements)
references
References 38 publications
30
293
2
Order By: Relevance
“…Consistent with observations made in LRRK2 KO rodents and nonhuman primates treated with less selective LRRK2 kinase inhibitors (Fuji et al, 2015), enlargement of type II pneumocytes (defined as very slight) was found in the lungs of all mice that received MLi-2 for 15 weeks. In addition to Ser935 dephosphorylation, we observed a significant reduction in total LRRK2 protein levels in the lung, although total LRRK2 levels were not completely ablated.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with observations made in LRRK2 KO rodents and nonhuman primates treated with less selective LRRK2 kinase inhibitors (Fuji et al, 2015), enlargement of type II pneumocytes (defined as very slight) was found in the lungs of all mice that received MLi-2 for 15 weeks. In addition to Ser935 dephosphorylation, we observed a significant reduction in total LRRK2 protein levels in the lung, although total LRRK2 levels were not completely ablated.…”
Section: Discussionsupporting
confidence: 88%
“…That LRRK2 inhibition by MLi-2 is well-tolerated by rodents agrees well with a recent report demonstrating good tolerability with another LRRK2 kinase inhibitor (PFE-06447475) after chronic administration (Daher et al, 2015). Both MLi-2 and PFE-06447475 have higher potency and selectivity for LRRK2 (Henderson et al, 2015) compared with GNE-0877 and GNE-7915 (Fuji et al, 2015), thus it seems probable that adverse effects observed with GNE-0877 and GNE-7915 are not LRRK2-mediated and are most probably the result of an as yet to be determined off target activity.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, the value of this therapeutic approach has been challenged by the observation that treatment with LRRK2 kinase inhibitors results in significant lung toxicity in primates (16). In addition, LRRK2 knockout rodent models display severe kidney phenotypes (17,18).…”
Section: Significancementioning
confidence: 99%